CONJUNCTION IN HEALTH COLUMNS OF CNN NEWS - Henny Marsito Situmorang; Noferman Halawa; Hiace Vega Fernando Siahaan (LPPM Universitas Darma Agung, 2022)
The goal of this study is to analyze “Conjunction in Health columns of CNN News”. The objectives of the study are to find out the types of conjunction, to find out the most dominant type and to find out the reasons of the most dominant type of conjunction used in health columns of CNN News. This thesis was conducted by using descriptive qualitative research. The writer explained about conjunction by giving the samples of sentence found in health columns of CNN News and then the writer also makes list of sentences by using percentage formula. Coordinating conjunction, correlative conjunction, subordinating conjunction and conjunctive adverb are analyzed by using Herring’s theory (2016). There are four types of conjunctions that is used in health columns of CNN News as the result., they are coordinating conjunction, correlative conjunction, subordinating conjunction and conjunctive adverb. After analyzing health columns of CNN News, the writer concludes that coordinating conjunction is the most dominant type of conjunction found in health columns of CNN News with the total occurrences as many as 60,66%. The reason of why coordinating conjunction was the most dominant type because coordinating conjunction is the most common form of conjunctions and it also used to join two or more words, phrases or independet clauses.